Burn induced nervous system morbidity among burn and non-burn trauma patients compared with non-injured people. Issue 5 (August 2019) - Duke, Janine M.; Randall, Sean M.; Fear, Mark W.; Boyd, James H.; Rea, Suzanne; Wood, Fiona M.
Highlights: Higher nervous system admission rates observed for previously burned patients vs. uninjured. Observed nervous system admission rates higher after burn than non-burn trauma. Further research needed to investigate link between injury and nervous system admissions. Abstract: Objective: Burns cause acute damage to the peripheral nervous system with published reports identifying that neurological changes after injury remain for a prolonged period. To shed some light on potential mechanisms, we assessed injury etiology and patterns of nervous system morbidity after injury by comparing long-term hospital admissions data of burns patients and other non-burn trauma patients with uninjured people. Methods: Linked hospital and death data of a burn patient cohort (n = 30, 997) in Western Australia during the period 1980–2012 were analysed along with two age and gender frequency matched comparison cohorts: non-burn trauma patients (n = 28, 647) and; non-injured people (n = 123, 399). The number of annual NS disease admissions and length of stay (LOS) were used as outcome measures. Multivariable negative binomial regression modelling was used to derive adjusted incidence rate ratios and 95% confidence intervals (IRR, 95% CI) and adjusted Cox regression models and hazard ratios (HR) were used to examine time to first nervous system admission after burn and incident admission rates. Results: The most common peripheral nervous system condition identified in each cohort (burn, non-burn trauma, uninjured) were episodic and paroxysmal disorders followed by nerve root and plexus disorders and polyneuropathies/peripheral NS conditions. Significantly elevated admission rates for NS conditions (IRR, 95% CI) were found for the burn (2.20, 1.86–2.61) and non-burn trauma (1.85, 1.51–2.27), compared to uninjured. Peripheral nervous system admission rates after injury (IRR, 95% CI) were significantly higher regardless of age at time of injury for the burn (<15years: 1.97, 1.49–2.61; 15–45: 2.70, 2.016–3.55; ≥45 year: 1.62, 1.33–1.97) and non-burn trauma cohorts (<15years: 1.91, 1.55–2.35; 15–45: 1.94, 1.51–2.49; ≥45 year: 1.42, 1.18–1.72), when compared to the uninjured. Significantly higher rates of incident NS hospitalisations were found for the burn cohort vs. uninjured cohort for a period of 15-years after discharge ( 0–5 years : HR, 95% CI: 1.97, 1.75–2.22; 5–15 years ; HR, 95% CI: 1.44, 1.28–1.63). The non-burn trauma cohort had significantly higher incident nervous system admissions for 10 years after discharge ( 0–30 days : HR, 95% CI: 4.75, 2.44–9.23; 30   days to 1-year HR, 95% CI: 2.95, 2.34–3.74; 1–5 years ; HR, 95% CI: 1.47, 1.26–1.70; 5–10 years ; HR, 95% CI: 1.34, 1.13–1.58). Conclusions: Results suggest that injury patients are at increased risk of peripheral nervous system morbidity after discharge for a prolonged period of time. The time patterns associated with incident nervous system conditions suggest possible differences in underlying pathology and long-term patient care needs. Further research is needed to elucidate the underlying neuropathology.